Climate changes and ST-elevation myocardial infarction treated with primary percutaneous coronary angioplasty. (1st November 2019) - Versaci, Francesco; Biondi-Zoccai, Giuseppe; Giudici, Angela Dei; Mariano, Enrica; Trivisonno, Antonio; Sciarretta, Sebastiano; Valenti, Valentina; Peruzzi, Mariangela; Cavarretta, Elena; Frati, Giacomo; Scappaticci, Massimiliano; Federici, Massimo; et al.
Abstract: Background: The impact of seasonal changes on the incidence of acute myocardial infarction has been incompletely appraised, especially in the modern era of primary percutaneous coronary intervention (PPCI). We aimed to appraise the overall and season-specific impact of climate changes on the daily rate of PCCI. Methods: Details on PPCI and climate changes were retrospectively collected in three high-volume Italian institutions with different geographical features. The association between rate of PPCI and temperature, atmospheric pressure (ATM), humidity and rainfall was appraised with Poisson models, with overall analyses and according to season of the year. Results: Details on 6880 days with a total of 4132 PPCI were collected. Overall adjusted analysis showed that higher minimum atmospheric pressure 3 days before PPCI were associated with lower risk (regression coefficient = 0.999 [95% confidence interval 0.998–1.000], p = 0.030). Focusing on season, in Winter PPCI rates were increased by lower same day mean temperature (0.973 [0.956–0.990], p = 0.002) and lower rainfall (0.980 [0.960–1.000], p = 0.049). Conversely, in Spring greater changes in atmospheric pressure 3 days before PPCI were associated with increased risk (1.023 [1.002–1.045], p = 0.032), with similar effects in Summer for minimum temperature on the same day (1.022 [1.001–1.044], p = 0.040). Conclusions: Climate has a significant impact on the risk of PPCI in the current era, with a complex interplay according to season. Higher risk risk is expected with lower minimum atmospheric pressure in the preceding days, lower rainfall in Winter, greater changes in atmospheric pressure in Spring, and higher temperatures in Summer. These findings have important implications for prevention strategies. Highlights: Acute myocardial infarction incidence may be impacted by climate changes. We appraised the impact of climate on rates of primary percutaneous coronary intervention. Climate impacted significantly on the risk of primary percutaneous coronary intervention. Risk correlated with atmospheric pressure in the preceding days and rainfall in Winter. Risk also correlated with atmospheric pressure in Spring, and higher temperatures in Summer.